SCIENTIFIC VALIDATION OF JATIPHALA AND JAVITRI IN HYPER PIGMENTATION - Yasmin, *S; Renu, Dixit; K.V.V Bhaskara, Reddy (International Journal of Ayurveda and Pharma Research, 2017)
Traditionally used medicinal plants have recently received the attention of the pharmaceutical and scientific communities. There is a need to develop new effective traditional drugs with scientific validation. The seed and aril of Jatiphala (Myristica fragrans Houtt.) of family Myristicaceae have the utilized therapeutically as medicine as well as a spice. Research into the scientific validation of nutmeg used in the treatment of Antidiarrheal, Hypnotic, Analgesic, Antimicrobial, Antidepressant and Sexual dysfunction has been done. In the present study Pharmacognostic study, Phytochemical study, Physico-chemical study and High performance thin layer chromatography are taken for the scientific validation of nutmeg.The Pharmacognostic study of macroscopic and microscopic identity of nutmeg was taken in order to set the quality standards of the market sample. The Phytochemical screening and its nutrients was done using Standarad methods. Qualitative analysis of Aqueous and Milk extracts of Seed and Aril of the nutmeg was studied for the presence of the Alkaloids, Carbohydrates, Proteins and Amino acids, Tannins, Saponins, Flavonoids and Fixed oils. Physico-chemical study involves the determination of identity, purity, and quality of nutmeg by the evaluation of Loss on Drying, Total Ash, Acid Insoluble Ash, Water Soluble Matter and Alcohol Soluble Matter parameters. High performance thin layer chromatography is one of the Sophisticated instrumental techniques for Identification and Quantitative determination of Phytochemical constituents of Seed and Aril part of the Nutmeg (Myristica fragrans Houtt).